Critical Developmental Stages for the Efficiency of Somatic Cell Nuclear Transfer in Zebrafish - Da-Ji Luo, Wei Hu, Shang-Ping Chen, Zuo-Yan Zhu (International Journal of Biological Sciences, 2011)
Somatic cell nuclear transfer (SCNT) has been performed extensively in fish since the 1960s with a generally low efficiency of approximately 1%. Little is known about somatic nuclear reprogramming in fish. Here, we utilized the zebrafish as a model to study reprogramming events of nuclei from tail, liver and kidney cells by SCNT. We produced a total of 4,796 reconstituted embryos and obtained a high survival rate of 58.9-67.4% initially at the 8-cell stage. The survival rate exhibited two steps of dramatic decrease, leading to 8.7-13.9% at the dome stage and to 1.5-2.96% by the shield stage. Concurrently, we observed that SCNT embryos displayed apparently delayed development also at the two stages, namely the dome stage (1:30 ± 0:40) and the shield stage (2:50 ± 0:50), indicating that the dome and shield stage are critical for the SCNT efficiency. Interestingly, we also revealed that an apparent alteration in klf4 and mycb expression occurred at the dome stage in SCNT embryos from all the three donor cell sources. Taken together, these results suggest that the dome stage is critical for the SCNT efficiency, and that alternated gene expression appears to be common to SCNT embryos independently of the donor cell types, suggesting that balanced mycb and klf4 expression at this stage is important for proper reprogramming of somatic nuclei in zebrafish SCNT embryos. Although the significant alteration in klf4 and mycb expression was not identified at the shield stage between ZD and SCNT embryos, the importance of reprogramming processes at the shield stage should not be underestimated in zebrafish SCNT embryos.